Applying TOGAF ADM for Developing an IT-Based Hedge Fund - Fawwazie, Muhammad Hilmy Haidar; Pradana, Firmansyah Putra; Pakaja, Fachrudin (oneamrd (One a Mllions Dreams Corporation), 2025)
This abstract describes the conceptual design of an enterprise architecture for a hedge fund. Sigma Investment Technologies faces operational challenges and the need for data-driven investment strategies alongside diversification into supporting services. The research objective is to design an enterprise architecture (EA) for Sigma Investment Technologies using TOGAF. A qualitative method with a conceptual case study approach is employed, based on requirements analysis from the business owner and industry best practices. The application of TOGAF resulted in a conceptual enterprise architecture design. This design demonstrates TOGAF's capability to map business elements structurally, covering core processes (such as R&D strategy, live trading, market research, and HPC for simulation) and supporting business processes. This EA design is expected to support decision-making, coordination, efficiency, risk management, and new monetization. It is concluded that this EA design provides a conceptual foundation for system development for modern hybrid hedge funds and can serve as a reference for the financial services industry, with the actual benefits anticipated upon full implementation.